Dampak Program Sekoper Cinta dalam Meningkatkan Ekonomi Keluarga - Rizky Putri Rosidin, Egie; Novia Ramdini, Nisa; Fauzia Nasril, Puji; Trijayanti, Armiati (Program Studi Pendidikan Luar Sekolah, 2023)
Abstract: This study aims to determite the impact of the Sekoper Cinta program in improving the family economy. In this study using qualitytative research methods with data collection techniques in the form og interviews, observation and documentation.This research takes a case study on the Sekoper Cinta program in the Gunung Tandala village area, Kawalu district of Tasikmalaya City. The Sekoper Cinta program has a positive impact on women, namely increasing access to education and skills training, an increase in the economy felt after participating in the Sekoper Cinta program. There are even those who are able to open up their business opportunities by utilizing the skills they gain from the training field while participating in the Sekoper Cinta program. Thus the impact of the Sekoper Cinta program is felt by every alumni of the Sekoper Cinta program, especially the benefits of knowledge and knowledge obtained during the implementation of the Sekoper Cinta program. With the Sekoper Cinta program, it can help women in improving the family economy so that many family economies are helped by the Sekoper Cinta program. Keywords: Women's Empowerment, Sekoper Cinta Program, Family Economy Abstrak: Penelitian ini bertujuan untuk mengetahui dampak program Sekoper Cinta dalam meningkatan ekonomi keluarga. Dalam penelitian ini menggunakan metode penelitian kualitatif dengan teknik pengumpulan data berupa wawancara, observasi dan dokumentasi. Penelitian ini mengambil studi kasus pada program Sekoper Cinta di daerah Kelurahan Gunung Tandala, Kecamatan Kawalu, Kota Tasikmalaya. Program Sekoper Cinta memberikan dampak positif bagi perempuan yaitu adanya peningkatan akses pendidikan dan pelatihan keterampilan, adanya peningkatan ekonomi yang dirasakan setelah mengikuti program Sekoper Cinta. Bahkan ada yang mampu membuka peluang usaha sendri dengan memanfaatkan kemampuan yang mereka peroleh dari bidang pelatihan selama mengikuti program Sekoper Cinta. Dengan demikian dampak program Sekoper Cinta sangat dirasakan oleh setiap alumni program Sekoper Cinta terutama manfaat ilmu dan pengetahuan yang diperoleh selama pelaksanaan program Sekoper Cinta serta memberikan dampak yang baik bagi perekonomian keluarga. Dengan adanya Program Sekoper Cinta dapat membantu kaum perempuan dalam meningkatkan ekonomi keluarga sehingga banyak perekonomian keluarga yang terbantu dengan adanya program Sekoper Cinta. Kata kunci: Pemberdayaan Perempuan, Program Sekoper Cinta, Ekonomi Keluarga